STRATEGI PENGEMBANGAN USAHA RUMAH TANGGA - Andi Fadhilah; Rahim Darma; A. Amrullah (Hasanuddin University, 2018)
This research has been done in Household Business “X”, which is located in Sidrap Regency, South Sulawesi. This research aims to: 1). Analyze the problems that happened in agrosystems case; 2). Analyze various solutions for problems in business development; 3). Formulate actions in achieving the objectives; 4). Implement selected actions. The whole data and information obtained in this research using the APPAS (Analysis of Agrosystem Design and Development) method and AHP (Analysis of Hierarchy Process). APPAS method is one of the learning methods that lead to overcome the problem in relation of the agrosystem case that used as the object of research and also directs to analyze the problem solving and AHP (Analysis Hierarchy Process) that is used to evaluate the alternative actions that must be done for the sake of development of agrosystem case. The result of the analysis shows that Household Business of “X” has the main problem that is Limited Marketing Area. The main problem happened due to the lack of promotion media, the manpower in the marketing department is unavailable, inadequate transportation, and limited equipment units. This main problem is the cause of low incomes, low demand, and low sales. To solve this problem, we have to set the main target that is increasing the revenue. The main target will be achieved if the media promotion increases, availability of manpower, transportation, and equipment units. Achieving the main targets will have an impact on increased of corporate revenue, the demand and the sales. Keywords: Strategy, Household Business, AHP (Analysis of Hierarchy Process)